Performance Evaluation on Fluidized Bed Reactor for the Treatment of Domestic Waste Water (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study was undertaken to study the performance of a Fluidized Bed Reactor in a sewage treatment plant and its efficiency to reduce the BOD, COD and TSS level. The physico-chemical parameters of the effluents like pH, Sulphate, Phosphate, Ammoniacal nitrogen, BOD, COD, TSS. TDS were analysed. Incorporating Fluidized Bed Reactor in the Sewage treatment plant allows the micro organisms to attach with the media in the bed resulting in accelerating the growth of organism thus increasing the degradation process of the organic waste improving the efficiency of STP. A physical model of STP with FBR was constructed – equalization tank, aeration tank, sedimentation tank and clear water tank. It is seen from the experimental work in the designed physical model of sewage treatment plant, the fluidized bed in aeration tank removal efficiency of BOD from 70-80 % . The removal efficiency based on the performance of FBR removal of COD ranges from 70 – 81 % and TSS ranged from 70- 85%. The colour of the effluent varied from dark brown to colourless. The overall evaluation of FBR treating the collected domestic waste water samples varies from 70 – 80% hence, the designed FBR is efficient